In vivo characterization of rate-dependent impact on the QT interval of microminipig assessed by atrial electrical pacing: Development of correction formulae of QT interval - KAMBAYASHI, Ryuichi (J Vet Med Sci, 2019)
Correction formulae of QT interval were developed for the halothane-anesthetized microminipigs by adopting atrial pacing (n=5), which were compared with Bazett’s and Fridericia’s formulae for humans, and Van de Water’s one for dogs. The correction formulae: QTc=QT−0.2072 (RR−750) as linear and QTc=QT/(RR/750)(0.4007) as non-linear equations, were developed for microminipigs. These formulae can better correct the QT interval of the microminipigs compared with each of the conventional ones for humans and dogs. Moreover, analysis of the slope constant α values indicates that the rate-dependent change in the ventricular repolarization period of microminipig may better mimic that of humans than that of dogs.